Evolution of visual performance in 70 eyes implanted with the Tecnis® ZMB00 multifocal intraocular lens - Palomino Bautista C (Dove Medical Press, 2012)
Carlos Palomino Bautista David Carmona González Alfredo Castillo GómezHospital Universitario Quirón, Madrid, SpainPurpose: To evaluate the development of visual acuity, dysphotopsia phenomena, and subjective sensations in patients implanted with the Tecnis® ZMB00 (Advanced Medical Optics Inc, Santa Ana, CA) multifocal intraocular lens.Methods: In a sample of 70 eyes, distance and near visual acuity, with and without correction, contrast sensitivity, and patient satisfaction, were analyzed at 15, 30, and 60 days post-surgery.Results: Mean uncorrected distance visual acuity (logarithm of minimum angle of resolution) at 15, 30, and 60 days was 0.194 ± 0.054, 0.119 ± 0.026, and 0.076 ± 0.014 (P < 0.0001), respectively, and with correction, 0.051 ± 0.007 vs 0.041 ± 0.004 vs 0.022 ± 0.002 (P < 0.0001), respectively). At 60 days, 94.3% of eyes could read 1.00 close-up without correction. Patient satisfaction in terms of dysphotopsia effects and visual acuity was excellent. The mean contrast sensitivity was 1.64 ± 0.10 (logarithmic units) measured with the Pelli–Robson test.Conclusion: This type of multifocal intraocular lens was very effective at the distances analyzed, producing excellent objective and subjective results.Keywords: higher-order aberrations, diffractive multifocal intraocular lens, visual acuity, dysphotopsia